Ammonia- and Nitrite-Oxidizing Bacteria are Dominant in Nitrification of Maize Rhizosphere Soil Following Combined Application of Biochar and Chemical Fertilizer - Sun, Ping; Zhao, Ziting; Fan, Pingshan; Chen, Wei; Ruan, Yunze; Wang, Qing (Frontiers in Microbiology, 2021)
Autotrophic nitrification is regulated by canonical ammonia-oxidizing archaea (AOA) and bacteria (AOB) and nitrite-oxidizing bacteria (NOB). To date, most studies have focused on the role of canonical ammonia oxidizers in nitrification while neglecting the NOB. In order to understand the impacts of combined biochar and chemical fertilizer addition on nitrification and associated nitrifiers in plant rhizosphere soil, we collected rhizosphere soil from maize field under four different treatments: no fertilization (CK), biochar (B), chemical nitrogen (N) + phosphorus (P) + potassium (K) fertilizers (NPK), and biochar + NPK fertilizers (B+NPK). The potential nitrification rate (PNR), community abundances and structures of AOA, AOB, complete ammonia-oxidizing bacteria (Comammox Nitrospira clade A), Nitrobacter-, and Nitrospira-like NOB were measured. Biochar and/or NPK additions increased soil pH and nutrient contents in rhizosphere soil. B, NPK, and B+NPK treatments significantly stimulated PNR and abundances of AOB, Comammox, and Nitrobacter- and Nitrospira-like NOB, with the highest values observed in the B+NPK treatment. Pearson correlation and random forest analyses predicted more importance of AOB, Comammox Nitrospira clade A, Nitrobacter- and Nitrospira-like NOB abundances over AOA on PNR. Biochar and/or NPK additions strongly altered whole nitrifying community structures. Redundancy analysis (RDA) showed that nitrifying community structures were significantly affected by multiple soil variables. This research shows that combined application of biochar and NPK fertilizer have a positive effect on improving soil nitrification by affecting communities of AOB and NOB in rhizosphere soil. These new revelations, especially as they related to understudied NOB, can be used to increase efficiency of agricultural land and resource management.